2009
DOI: 10.1017/s1352465809005256
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Evaluation of a Large-Scale Self-Referral CBT-I Intervention for Men Who Have Insomnia: An Exploratory Study

Abstract: Given these promising results, further work is now proposed for a larger controlled study with a longer-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
(33 reference statements)
5
19
0
Order By: Relevance
“…As hypothesised, on average insomnia reduced from the moderate insomnia range to sub--clinical levels of insomnia at four week follow--up, and this reduction represented a large effect size. This finding offers further supporting evidence for the effectiveness of CBT--I (Morin & Espie, 2003;2006a), as well as its effective delivery in the format of a one--day group workshop (Archer et al, 2009;Prytys et al, 2010;Swift et al, 2012). Greater reduction of insomnia symptoms was seen in those with more severe levels of insomnia at baseline, supporting the use of this format even with those individuals with more severe insomnia.…”
Section: Clinical Effectivenesssupporting
confidence: 57%
See 2 more Smart Citations
“…As hypothesised, on average insomnia reduced from the moderate insomnia range to sub--clinical levels of insomnia at four week follow--up, and this reduction represented a large effect size. This finding offers further supporting evidence for the effectiveness of CBT--I (Morin & Espie, 2003;2006a), as well as its effective delivery in the format of a one--day group workshop (Archer et al, 2009;Prytys et al, 2010;Swift et al, 2012). Greater reduction of insomnia symptoms was seen in those with more severe levels of insomnia at baseline, supporting the use of this format even with those individuals with more severe insomnia.…”
Section: Clinical Effectivenesssupporting
confidence: 57%
“…More recently this model has been applied, with success, to the treatment of insomnia (Archer et al, 2009;Prytys et al, 2010). Swift and colleagues (2012) report the results of a randomised controlled trial (RCT) showing significant reductions in clinical levels of insomnia in those who attended a CBT--I workshop compared with waitlist controls.…”
Section: Access To Treatment For Insomniamentioning
confidence: 99%
See 1 more Smart Citation
“…An exploratory study found that for a community sample of men with sleep difficulties, this approach was associated with improvements in both insomnia and depression symptoms (Archer et al, 2009). In a randomized controlled trial that Swift et al (2012Swift et al ( ) conducted in 2008Swift et al ( -2009, participants who attended a one-day, self-referral CBT workshop for sleep difficulties were compared with a control group on insomnia severity three months after baseline.…”
mentioning
confidence: 99%
“…The main objective of this study was to carry out a qualitative investigation using a sample of adults who had participated in the randomized controlled trial of a CBT-I intervention cited above (Swift et al, 2012). This large-scale workshop format has demonstrated success in improving insomnia and depression symptoms (Archer et al, 2009) and may last for up to two years (Brown et al, 2008). However, we do not know how participants explain the changes that have been observed over time and if these changes are associated with workshop-specific or more general factors.…”
mentioning
confidence: 99%